2020
DOI: 10.20396/bjos.v19i0.8658591
|View full text |Cite
|
Sign up to set email alerts
|

#Dentalpain

Abstract: Aim: The aim of this study was to evaluate what brazilian Instagram® users manifest when they use #dordedente (#dentalpain in portuguese). Methods: The content of 1,000 publications related to dental pain was evaluated. Through print screens posts were collected in two periods (2015 and 2020) and organized into files. Variables related to characteristics of users, publication’s type, cause of pain, impact on daily life and actions take to relieve pain were collected. Data analysis was realized through the qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…Results of a research in oral health also showed that the Instagram social network is an efficient means of communication, being both an alternative to disseminate health information and a tool for health surveillance ( 33 ) . It is easily accessible, with a wide audience, and can be used to disseminate quality and reliable information ( 27 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Results of a research in oral health also showed that the Instagram social network is an efficient means of communication, being both an alternative to disseminate health information and a tool for health surveillance ( 33 ) . It is easily accessible, with a wide audience, and can be used to disseminate quality and reliable information ( 27 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Resultados de uma pesquisa na área de saúde bucal também evidenciou que a rede social Instagram é um meio de comunicação eficiente, sendo tanto uma alternativa para divulgar informações em saúde quanto um instrumento de vigilância à saúde (33) . Ele é de fácil acesso, com público abrangente, podendo ser utilizado para disseminar informações de qualidade e fidedignas (27) .…”
Section: Discussionunclassified